Dari UJB untuk Padukuhan Kemusuh: Meningkatkan Potensial dan Kemampuan Masyarakat dalam Upaya Memajukan UMKM Setempat untuk Menyongsong Dampak Adanya Ruas Jalan Tol Yogyakarta-Bawen - Fauzan Rayyan Zukair; Alfina Windarningrum; Natalya Nustelu; Retniana Bau; Marthinus Rudy Loimera; Fredy Tatogo; Rudolof Tenau; Luchio Alesandro Mbaga; Deri Andri Simbolon; Ari Ahmad Syukuri; Danang Sunyoto (Lembaga Pengembangan Kinerja Dosen, 2025)
The 2025 Thematic Community Service Program (KKN-T) of Group R2 from Janabadra University Yogyakarta was carried out in Kemusuh Hamlet, Banyurejo Village, Tempel Sub-district, Sleman Regency. The main objective of this program was to develop the potential and enhance the capabilities of the local community in managing Micro, Small, and Medium Enterprises (MSMEs), particularly in response to the economic impacts of the ongoing construction of the Yogyakarta–Bawen toll road near the area. Through a participatory approach and methods such as field observation, needs analysis, and solution implementation, the students aimed to empower the community to adapt to future economic changes. Key programs included training in financial management, digital wallet creation, product and packaging design, and the use of Google Maps for business promotion. The results showed improvements in awareness, skills, and readiness of the community to manage their businesses independently and remain competitive in the digital era.